Potential of multimodal and multiuser interaction with virtual holography. (March 2015) - Noor, Ahmed K.; Aras, Rifat
Abstract: Virtual holography is a disruptive technology that can inspire innovations in variety of fields through blending the physical world with sensory-rich virtual world. The technology enables users to naturally and intuitively manipulate objects and navigate in 3D space. The zSpace virtual holography platform is described. The platform provides a 3D display and head-tracking technology that transforms PCs into virtual-holographic computing facility using a stereoscopic user interface with an interactive stylus. The major components of the platform and its potential benefits, along with some of the current applications are briefly described. The use of the zSpace platform to explore and manipulate a number of space system models is outlined. The models considered include Titan Saturn system, a joint NASA/ESA mission; Mars Science Lab concept; James Webb Telescope; and a Lunar Lander concept. In each of the applications considered, the platform is enhanced by using multimodal interactions, and providing support for multiuser collaboration. The multimodal interactions, which enable more engaging, enhanced accessibility, are achieved by fusing information from a set of stylus input, 3D gestures, and neural input. Simultaneous and collaborative multiuser interactions are described, which support both local and distributed teams, using variety of displays. Emerging and future enhancements of the zSpace platform are outlined, along with novel future applications.